Surveying the UNIPREP Orientation Program at the University of New South Wales: The Beginning of the Transition Process Into University - Julie Erskine (JANZSSA)
The Counselling Service at the University of New South Wales co-ordinates an orientation program, UNIPREP, for its incoming students. The aim is to help prepare students, both academically and socially, for their transition into University life. Both before and after the 1998 and 1999 UNIPREP Programs, students were surveyed to assess the effectiveness of the Program. While attendance varied across the different activities offered during orientation, students consistently reported the activities to be useful or very useful. Overall usefulness of the program was also reported as well as reasons for non-attendance. Results indicated that students‟ expectations of the Program were met and satisfaction with the Program was high. Recommendations were also given based on the results.